Kazakhstan : Note on Senior Civil Service Pay - World Bank (Washington, DC, 2014)
This report examines the pay-setting arrangements for senior civil servants in three settings: the Netherlands, the United Kingdom and Singapore. It concludes that: a robust analytic approach for pay setting seems to be sufficient to maintain some general sense of legitimacy in the process, but is not the dominant driver of pay levels; external consultancies are employed significantly to obtain data on salaries for comparable positions in the private sector; the hay method is used in many settings and the World Bank analytic approach is not dissimilar to that used in many governments; however, governments are different to the World Bank in some critical ways. Like the Bank, they are driven by the need to establish a system which is seen to be legitimate both to staff and to the funders; thus, while the institutional arrangements for managing and overseeing the pay-setting process are, also, very much concerned with ensuring legitimacy for the resultant pay settlement, and so involve some significant delegation to signal that the recommendations are somewhat independent, the final decision for pay is ultimately made by government on political as well as fiscal and economic grounds; and the numbers of political advisors outside of the formal schemes is modest and does not seem to have a strong influence on the pay-setting process for senior staff in the settings studied.